The Development of Windows Communication Foundation Application as Middleware for Banyumas Tourism and Culinary Information System - Yuli Purwati; Fandy Setyo Utomo (Universitas Ahmad Dahlan, 2014)
Banyumas located in the southwest of Central Java province. Banyumas is a tourist destination that serves a variety of interesting attractions to visit which include natural attractions, arts and culture, as well as culinary tourism. Business growth in the culinary and hospitality sectors in Banyumas region since 2011 experienced a significant increase in terms of quantity. Two of the business sector is a potential contributing factor for the tourism sector in Banyumas. In this study, an attempt to introduce and market potential for tourism, arts and culture, as well as culinary Banyumas done through WCF as a middleware application development that can be used by client applications to provide information about the potential of tourism, arts and culture, as well as culinary Banyumas. Step study conducted starting from data collection, analysis of functional requirements, system design, implementation, and testing of WCF applications. WCF application consists of several services, namely download service information lists attractions, arts and cultural information, culinary information, lodging information, and download the tourism image data from the server. Based on the test results of the service, it can be concluded that the service to function properly and is able to distribute information to the client.